Шығармашылық әлеует – мұғалімнің кәсіби мәнді сапаларының бірі - Бұлақбаева, М.К.; Қондыбаева, Х. (My University, 2013)
In this article creative potential is examined as one of professionally-meaningful qualities of teacher.